In Utero Exposure to Di(n-butyl)phthalate Induces Morphological and Biochemical Changes in Rats Postpuberty. (June 2017) - Okayama, Yuya; Wakui, Shin; Wempe, Michael F.; Sugiyama, Mitsuru; Motohashi, Masaya; Mutou, Tomoko; Takahashi, Hiroyuki; Kume, Eisuke; Ikegami, Hiroshi
Pregnant Sprague-Dawley rats were orally administered di( n -butyl)phthalate (DBP; 100 mg/kg/day) on gestation days (GD) 12 to 21. We investigated the male offspring and probed morphological alterations in Sertoli cells at 7, 9, 14, and 17 weeks of age. Parameters assessed in this study included offspring number, sex ratios, body weights, testis weights, seminiferous tubule (ST) profile numbers and diameters, number of vimentin-labeled Sertoli cells, and both testosterone and follicle-stimulating hormone (FSH) levels. Testicular weight/body weight ratios and the numbers and diameters of ST in maximum transverse testicular sections were statistically similar at weeks 7 and 9; however, at weeks 14 and 17, they were statistically different and displayed higher BrdU-positive Sertoli cells/Sertoli cell ratios in the DBP treatment group. Noteworthily, the serum FSH levels were higher and testicular testosterone levels were lower in the DBP treatment group. To our knowledge, the present study is the first to report that in utero DBP exposure significantly increased Sertoli cell numbers and their cellular proliferation from postpuberty to adulthood, with a significant decrease in testicular testosterone and an increase in FSH.